2003
DOI: 10.1063/1.1527630
|View full text |Cite
|
Sign up to set email alerts
|

Observation of faster-than-diffusion magnetic field penetration into a plasma

Abstract: Spatially and temporally resolved spectroscopic measurements of the magnetic field, electron density, and turbulent electric fields are used to study the interaction between a pulsed magnetic field and a plasma. In the configuration studied (known as a plasma opening switch) a 150 kA current of 400 ns-duration is conducted through a plasma that fills the region between two planar electrodes. The time-dependent magnetic field, determined from Zeeman splitting, is mapped in three dimensions, showing that the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 47 publications
2
57
2
Order By: Relevance
“…Previous spectroscopic measurements of the electron density have shown a density rise of up to $50%, which generally accompanies the arrival of the magnetic field to the region of observation, followed by a sharp density drop. 30 This observation was consistent with earlier line-integrated density measurement in similar systems. 32,33 The spatially resolved spectroscopic measurements showed that part of the plasma is indeed penetrated by the magnetic field and remains behind the propagating field front.…”
supporting
confidence: 82%
See 4 more Smart Citations
“…Previous spectroscopic measurements of the electron density have shown a density rise of up to $50%, which generally accompanies the arrival of the magnetic field to the region of observation, followed by a sharp density drop. 30 This observation was consistent with earlier line-integrated density measurement in similar systems. 32,33 The spatially resolved spectroscopic measurements showed that part of the plasma is indeed penetrated by the magnetic field and remains behind the propagating field front.…”
supporting
confidence: 82%
“…2016) profile. 30 It was shown, under similar conditions, that ionization processes (due to the electron heating resulting from the magnetic energy dissipation) and the continuous plasma flow from the flashboard-plasma source cannot account for more than $30%-rise in n e during the magnetic field penetration. The significant additional density-rise observed was attributed to the proton reflection, a process later verified using charge exchange measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations